2015
DOI: 10.1152/ajpheart.00260.2015
|View full text |Cite
|
Sign up to set email alerts
|

Roles of store-operated Ca2+channels in regulating cell cycling and migration of human cardiac c-kit+progenitor cells

Abstract: Cardiac c-kit(+) progenitor cells are important for maintaining cardiac homeostasis and can potentially contribute to myocardial repair. However, cellular physiology of human cardiac c-kit(+) progenitor cells is not well understood. The present study investigates the functional store-operated Ca(2+) entry (SOCE) channels and the potential role in regulating cell cycling and migration using confocal microscopy, RT-PCR, Western blot, coimmunoprecipitation, cell proliferation, and migration assays. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…The cell viability was determined with MTT assay as described previously [51, 52]. Briefly, human coronary artery SMCs were seeded in 96-well plates (Thermo Fisher Scientific, MA, USA) for 24 h and incubated with medium containing 5% FBS and different concentrations of lypoPC or equal volume of vehicle (ethanol, Sigma-Aldrich) for different period of time.…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…The cell viability was determined with MTT assay as described previously [51, 52]. Briefly, human coronary artery SMCs were seeded in 96-well plates (Thermo Fisher Scientific, MA, USA) for 24 h and incubated with medium containing 5% FBS and different concentrations of lypoPC or equal volume of vehicle (ethanol, Sigma-Aldrich) for different period of time.…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…Our recent study demonstrated that TRPC1, Orai1 and STIM1 are components of SOCE channel complex in human cardiac c‐Kit + progenitor cells 13. If bradykinin‐induced Ca 2+ influx is mediated solely by TRPC1 channel, the effect would not be affected in cells with silenced Orai1 or STIM1.…”
Section: Resultsmentioning
confidence: 97%
“…We have recently demonstrated that SOCE channel participates in regulating cell growth and migration,13 and bradykinin promotes cell cycling progression and mobility in cultured human cardiac c‐Kit + progenitor cells 10. To investigate whether the stimulation of cell cycling progression and mobility by bradykinin is related to Ca 2+ signalling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations